Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan: Survey Pada Salah Satu Penyedia Jasa Internet di Kota Bandung - Desi Rismawati; Irena Larashati; Dudung Juhana (Majalah Bisnis & IPTEK, 2021)
The results of this study were carried out to know the effect of price and service quality on customer satisfaction. The study used a survey approach to internet service customers as many as 100 people in the city of Bandung. Based on research using path analysis, it appears that the price variable has a direct influence of 14.7%. The indirect effect through the service quality variable is 13.1%, the total effect is 27.9%. On the other hand, service quality variables directly influence 32.1%. The indirect effect through the variable price is 13.1%, the total effect is 45.2%. The coefficient of determination (R-square) relationship expressed in the percentage of the contribution of all independent variables price and service quality in determining customer satisfaction variables is 73.1%. In comparison, other factors that affect customer satisfaction not examined shown by the value Є = 0.269 Or 26.9%. The recommendation is that the company should further improve the quality of the internet and other products to improve customer satisfaction.